Resonant emission in four-wave mixing for a cycling transition Fg = 1 ↔ Fe = 0 - Sun, Qingqing; Gu, Ying; Gong, Qihuang (Journal of modern optics, 2006)
Four-wave mixing (FWM) in a cycling transition F g =1 ↔ F e =0 is investigated. Subject to a linearly polarized pump field with frequency ω c and a magnetic field, and simultaneously saturated and probed by the circularly polarized fields (σ ± ) with frequencies ω s and ω p , three kinds of FWM fields with frequencies: 2ω s − ω p , ω c +ω s − ω p and ω c − ω s +ω p , emit. The multi-peaked structure of FWM spectra is obtained and explained as the resonant emission between the 'virtual states' in the dressed picture. The generated FMW signals have high quantum efficiency for a wide range of drive Rabi frequency and saturation Rabi frequency. Finally, the emitted fields ω c + ω s − ω p and ω c − ω s +ω p have about the same intensity for the well matching among the Zeeman splitting, drive Rabi frequency and saturation Rabi frequency.